Close Proximity of Leadless Pacemaker to Tricuspid Annulus Predicts Worse Tricuspid Regurgitation Following Septal Implantation. (18th May 2021) - Hai, Jo-Jo; Mao, Yankai; Zhen, Zhe; Fang, Jonathan; Wong, Chun-Ka; Siu, Chung-Wah; Yiu, Kai-Hang; Lau, Chu-Pak; Tse, Hung-Fat
Abstract : Supplemental Digital Content is available in the text.